A New Technique for Sagittal Synostosis: A Plurality of Small Incisions Minimally Invasive Technique Used on Infants and Young Patients. Issue 8 (November 2018) - Liu, Tian-Jia; Wu, Shui-Hua; Fan, Shuang-Shi; Chen, Zhao-Hui; Gu, Shuo
Abstract : Objectiv: The authors devised a multiple small incisions minimally invasive technique for use in isolated nonsyndromic sagittal synostosis to achieve better esthetic effect and satisfactory reshaping of the calvarial vault. The purpose of this study is to provide clinicians with new and feasible solution. Methods: From April 2016 to January 2017, 5 male patients were successfully treated with minimally invasive surgery. The age ranges from 1.5 to 3.3 years. The authors designed 9 short skin linear incisions (2–3 cm long) strategically to disperse in the scalp. The patient was assessed in a series including sex, age of surgery, blood loss, blood transfusion, duration of surgery, postoperative complications, preoperative and postoperative cephalic index (CI), length of stay (LOS), esthetic outcomes, and intellectual developmental quotient (DQ). Results: The shortest operation time is 1.5 hours. The shortest hospital stay is 6 days. The blood loss ranged from 135 to 280 mL. No serious complications occurred during the follow-up time. Postoperative 3-dimensional CT scan showed that the extensive floating bone formed well. Preoperative CI ranged from 64.2 to 68 and postoperatively 69.4 to 74.3. Mental development was tested by children heath care practioners, significantly improving DQ from 67 to 81 preoperatively and 76 to 90 postoperatively. All children receive good esthetic results. Conclusion: The new technique is safe and effective. The advantages are satisfactory: calvarial fornix remodeling, less visible appearance of scars, shorter length of surgery, lower mental and financial stress, optimal age for surgery, no endoscopic adjuvant and postoperative helmet are needed.